Multicomponent laser coating developed on Ti-6Al-4V using hBN, Ni-coated-graphite, Ni and Ti powders for improving tribological performance. (2018) - Haldar, Barun; Srivastva, Vikash K.; Keshvendra, Kumar; Saha, P.
Abstract: Multicomponent coating development is one of the present research trends in surface engineering applications. Favorable characteristics of multicomponent laser coatings are advantageous for prolonging tribological service life of wear parts. Low hardness and poor wear resistance of Ti-6Al-4V surface were enriched by developing laser coatings. In this present work, the pre-placed powder mixtures of h BN, Graphite, Nickel coated graphite, Nickel-Titanium were laser irradiated to form multicomponent coatings. The physical characterizations of the coatings were done under SEM, EDS and HR XRD analysis. Dry-sliding-wear performance was tested and significantly low coefficient of friction (0.15)was noted on the laser coated samples.